2009
DOI: 10.1007/s11814-009-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

CO2 gasification of Thai coal chars: Kinetics and reactivity studies

Abstract: Two sized fractions (<75 µm and 150-250 µm) of Ban Pu lignite A and Lampang subbituminous B coals were pyrolyzed in a drop tube fixed bed reactor under nitrogen atmosphere at 500-900 o C. Gasification of coal chars with excess carbon dioxide was then performed at 900-1,100 o C. The result was analyzed in terms of reactivity index, reaction rate and activation energy. It was found that chars at lower pyrolysis temperature had highest carbon conversion, and for chars of the same sized fraction and at the same py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The reactivity index (R) of the char was calculated from eq 4. 25,26 This definition is widely used in the literature for comparison of reactivity of different coals…”
Section: Char Combustion Reactivitymentioning
confidence: 99%
“…The reactivity index (R) of the char was calculated from eq 4. 25,26 This definition is widely used in the literature for comparison of reactivity of different coals…”
Section: Char Combustion Reactivitymentioning
confidence: 99%
“…The reactivity of char produced at the lowest pyrolysis temperature was found to be the highest, and the chars produced at the same pyrolysis temperature showed higher conversion at a given time with increasing gasification temperature. However, Wu et al contradicted the effect of pyrolysis temperature on the gasification reactivity of coal char in a CO 2 atmosphere as observed by Sawettaporn et al Li et al investigated experimentally Chinese bituminous coal char of particle size of less than 150 μm at a temperature range of 970–1150 °C in CO 2 . They reported that an increase in gasification temperature significantly increases carbon conversion and reduces the complete conversion time.…”
Section: Introductionmentioning
confidence: 99%
“…Varying physicochemical properties of different carbonaceous materials affect the gasification reactivity in the presence of CO 2 . Sawettaporn et al 7 carried out the experimental investigation on the gasification of two different types of coal chars (Ban Pu lignite A and Lampang sub-bituminous B) in the size range of 75−250 μm in a pure CO 2 atmosphere at the temperature range of 900−1100 °C. The char was prepared in the drop tube fixed-bed reactor under nitrogen flow in the temperature range of 500−900 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the investigation of coal gasification and combustion reactivity with a CO 2 atmosphere will be an essential feature to allow the understanding of the reaction mechanism and kinetics for the development of the gasification technology. The CO 2 gasification study on coal, biomass and other carbonaceous materials has been extensively investigated using thermogravimetric analysis (TGA) (Ergun 1956;Zhang et al 2006;Sawettaporn et al 2009;Kim et al 2011;Ng et al 2011;Yuan et al 2011;Lahijani et al 2012;Jing et al 2013;Kuznetsov et al 2013;Skodras 2013;Wei et al 2014). However, the CO 2 gasification data of Indian coals is found to be limited and in need of urgent attention (Saha et al 2012;Sahu 2013;Mishra et al 2014;Aranda et al 2016).…”
Section: Introductionmentioning
confidence: 99%